Grain refinement of DHP copper by elemental additions. (August 2015) - Balart, M. J.; Patel, J. B.; Gao, F.; Fan, Z.
<x content-type="archive" xml:space="preserve">Abstract</x> The effects of additions of P and Ag, as well as the de-embrittling elements of copper—B, Mg, Ca, Ti and Zr—in concentrations of 0.085–0.5 wt-% to give some variations in contents within and outside of the DHP specification limits on grain size structure have been investigated under TP-1 casting conditions. Columnar to equiaxed transition has been observed with combined additions of 0.1%Ag–0.069%P; 0.4%Zr–0.039%P and with an addition of 0.5%B and, to a lesser extent, with an addition of 0.1%P and with combined additions of 0.4%Ag–0.030%P and 0.085%Ti–0.039%P. In contrast, 0.085% additions of Mg, Ca and Zr to DHP-Cu as well as 0.4%Ti to Cu failed to achieve grain refinement. Excessive coarsening of equiaxed grains has been observed with additions of 0.085–0.17%B, 0.4%Mg, 0.4%Ca and 0.5%P. Those results suggest making the maximum additions of P of 400 ppm and of Ag of 150 ppm to DHP-Cu for grain size control.